Juridical Analysis of Court Determinations on Land Acquisition Consignment - Taqiy Nurdaiman; Diyan Isnaeni; Sunardi (Jurnal Cakrawala Hukum, 2024)
In the implementation of the Deliberation on the Form and/or Amount of Compensation in the Land Acquisition of Dhoho Kediri International Airport, there are Rights Holders who disagree with the deliberations; the Rights Holders who disagree do not submit an Objection to the local District Court, until finally, the Land Acquisition Implementer makes an Application for Custody of Compensation through the Court. The validity of the Compensation Custody through the Court is reviewed from Law Number 2 of 2012 and the legal consequences of the issuance of the Court Determination. This research uses a normative juridical method, which analyzes a legal problem using laws, books, journals, and other written works with legal standing. This study concludes that the Court accepted the Consignment Application because the Right Holder, who disagreed with the results of the Deliberation on the amount of compensation, did not file an objection to the District Court 14 days after the holding of the Deliberation on the Form and/or Amount of Compensation Agreement, and its existence could not be found. The validity is absolute, considering that the Land Acquisition Implementer has fulfilled the conditions of the Application. Regarding the legal consequences of the Court Determination, it is considered to be the termination of the legal relationship between the Right Holder and its land, it is deemed to be handing over the right to its land to the State, and the nature of the Determination is final so it must be accepted and implemented by all parties. In the end, the Right Holder accepted the results of the Consignment and was also present in the execution of the object in question.